Ernst Engel's Law of Expenditures for Food - Zimmerman, Carle C. (Quarterly Journal of Economics, 1932)
Erroneous statements of the law, 78.— The correct version, 79.— The validity of the law: theoretical considerations, 86; the conclusions to be drawn from the facts, 87.— Reasons for these results, 95.— Implications of the study, 100.— Conclusion, 101.